Human-wildlife conflicts in Iberian waters : Orcinus Orca and vessels encounters from a socio-ecological systems approach - Sophie Martel 1991- (2024)
Since 2020 members of the Iberian Orcinus orca subpopulation have sparked media attention for their sudden interference with small vessels, particularly sailboats and their rudders. The development of this behaviour, qualified as unusual and disruptive, has been at the heart of scientific research aiming at finding its causes and preventive measures. However, damaged and sunken boats have heightened the sailors’ concerns for their safety and led to tensions along the Portuguese and Spanish coasts particularly. The conflictual dynamics resulting from these encounters emphasise the need to incorporate the human dimension and the complexity of multimodal needs in conservation strategies. Addressing this case study through a socio-ecological systems approach is an opportunity to give visibility to the interactivity of human and nature connections. With Ostrom’s framework as a guiding methodology and overarching tool, this research was conducted using a combination of ecological secondary data collection, through media content and cetacean literature review and primary social data collection through surveys and interviews. The results contribute to a cross-scale overview of the Iberian orcas, highlighting familiar cetacean characteristics as potential drivers of interactive behaviour, and uncovering layers of human dimension shaped by perception, culture, and social inclinations of the main stakeholders, the sailors. Ultimately, this research is an example of an interdisciplinary proposal encouraging convergence and collaboration in order to move away from human-wildlife conflict dynamics. Appreciating the influential importance of both social and ecological systems, policies are recommended to, on the one hand, not underestimate the impact of human relations on conservation narratives, and, on the other hand, to consider the actors of the ecological systems as active players and stakeholders in resource management strategies, offering a socio-ecosystem-based management approach with focus on fostering coexistence. ...